Alpine glacier algal bloom during a record melt year - Millar, Jasmin L.; Broadwell, Emily L. M.; Lewis, Madeleine; Bowles, Alexander M. C.; Tedstone, Andrew J.; Williamson, Christopher J. (Frontiers in Microbiology, 2024)
Glacier algal blooms dominate the surfaces of glaciers and ice sheets during summer melt seasons, with larger blooms anticipated in years that experience the greatest melt. Here, we characterize the glacier algal bloom proliferating on Morteratsch glacier, Switzerland, during the record 2022 melt season, when the Swiss Alps lost ~3-times more ice than the decadal average. Glacier algal cellular abundance (cells ml -1 ), biovolume (µm 3 cells -1 ), photophysiology (Fv/Fm, rETRmax) and stoichiometry (C:N ratios) were constrained across three elevations on Morteratsch glacier during late August 2022 and compared to measurements of aqueous geochemistry and outputs of nutrient spiking experiments.While a substantial glacier algal bloom was apparent during summer 2022, abundances ranged 1.78 ×10 4 to 8.95 ×10 5 cells mL -1 of meltwater and did not scale linearly with the magnitude of the 2022 melt season. Instead, spatiotemporal heterogeneity in algal distribution across Morteratsch glacier leads us to propose melt-water-redistribution of (larger) glacier algal cells down-glacier and presumptive export of cells from the system as an important mechanism to set overall bloom carrying capacity on steep valley glaciers during high melt years. Despite the paradox of abundant glacier algae within seemingly oligotrophic surface ice, we found no evidence for inorganic nutrient limitation as an important bottom-up control within our study site, supporting our hypothesis above. Fundamental physical constraints may thus cap bloom carrying capacities on valley glaciers as 21 st century melting continues.